LOYALITAS EMOSIONAL DAN KETERLIBATAN KOMUNITAS: STUDI KARAKTERISTIK FANATISME PENGGEMAR MUSIK KAPAL UDARA BAND - Nabhan Rizqan Fathana; M. Ramli AT; Ridwan Syam (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the level of fandom among supporters of Kapal Udara Band in Makassar City through three indicators: imitation, consumptive behavior, and obsession. A descriptive quantitative method was employed, with a sample of 72 respondents selected using Slovin’s technique. Results indicate a